The genus Armadillo Latreille, 1802 (Oniscidea, Armadillidae) from Cyprus, with descriptions of two new species - Campos-Filho, Ivanklin Soares; Dimitriou, Andreas C.; Taiti, Stefano; Sfenthourakis, Spyros (Zootaxa, 2023)
The present work aims to morphologically characterize the species of Armadillo from Cyprus. Moreover, two new species of the genus are described, A. konstantinoui sp. nov. from several places along the island, and A. karametae sp. nov. from Pafos region. The circum-Mediterranean species A. officinalis is also redescribed.